Impact of cultural positions on FDI's entry mode. Issue 3 (3rd August 2015) - López-Duarte, Cristina; Vidal-Suárez, Marta M.; González-Díaz, Belén
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to study the influence of cultural positions on the choice of entry mode in foreign direct investment (FDI) – joint ventures vs wholly owned subsidiaries. The paper focusses on the impact of cultural positions along four cultural dimensions, as well as on the interactions between these positions and FDI's contextual variables (i.e. linguistic differences). Design/methodology/approach – A fuzzy set qualitative comparative analysis is performed on a data set of Spanish investments located in the European Union. Findings – Existence of interaction effects among cultural positions along different dimensions, as well as between cultural positions and FDI's contextual variables. Research limitations/implications – Main limitations relate to the data set, as only FDIS carried out by big corporations and coming from a single country are considered. Practical implications – Managers making decisions on the choice of entry mode must take into account the position relative to each individual cultural dimension, as well as its interaction with other cultural dimensions and FDI's contextual variables, rather than just considering cultural distances (CDs) between countries. Originality/value – First, focus on cultural positions (rather than CDs). It allows taking into account both the cultural characteristics of each party and their relative values along individual cultural dimensions. Second, development of a qualitative analysis that considers the contextual features of the investment.